Impact of mobilization regimen on multiday collection of peripheral blood CD34+ cells by large volume leukapheresis. Issue 4 (25th February 2022) - Siddiqui, Irmeen; Shmookler, Aaron; Biller, Elizabeth; Hardy, Tanner; Hartage, Ramon; Losos, Michael; Chen, Jian
Abstract: Background: The collection yield of hematopoietic progenitors cell (HPC) by leukapheresis is critical for a successful transplantation, which often requires multiday collections to achieve the collection goal. Study Design and Methods: Collection procedures of 181 patients who underwent leukapheresis for more than 1 day were reviewed. Patients were separated into six groups based on the mobilization regimen: G‐CSF on day 1 (D1) and day 2 (D2) (G‐G); G‐CSF on D1 and G‐CSF and plerixafor on D2 (G‐GP); G‐CSF and plerixafor on day D1 and D2 (GP‐GP); G‐CSF and plerixafor on D1 and G‐CSF on D2 (GP‐G); chemotherapy and G‐CSF on D1 and D2 (GC‐GC); and chemotherapy, G‐CSF, and plerixafor on D1 and D2 (GCP‐GCP). Patient's pre‐collection CD34 count (pre‐CD34) on D1 and D2 were compared in the same individual and among groups. Results: We found D2 pre‐CD34 were significantly decreased in G‐G, GP‐G, and GP‐GP groups and significantly increased in G‐GP group ( p  < .001) using a repeated measures ANOVA analysis. D2 pre‐CD34 remained at similar levels as D1 in GC‐GC and GCP‐GCP groups. A multiple regression analysis showed that the mobilization regimen was the only factor that significantly affected pre‐CD34 D2/D1 ratio ( p  < .001). There was a significant difference in the pre‐CD34 D2/D1 ratio ( p  < .001) among these six groups with the lowest in GP‐G group (0.40 ± 0.45), and the highest in G‐GP group (2.35 ± 0.36). Discussion: Mobilization regimen has significant impact on pre‐collection CD34 count. Apheresis facilities may change mobilizing drugs accordingly to achieve a specific HPC goal.